PENGARUH TINGKAT PEMAHAMAN, KEPATUHAN DAN KETEGASAN SANKSI PERPAJAKAN TERHADAP KEWAJIBAN PERPAJAKAN UMKM DI KOTA MALANG - Muhammad Erdin Riduwani; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the effect of the level of understanding, compliance and firmness of tax sanctions on the taxation obligations of MSME in Malang City. The population in this study is the taxpayers of MSME actors who are registered at the Tax Office (KPP) Pratama Malang Utara. This study uses quantitative research to take primary data which is taken through distributing questionnaires to taxpayers of MSME actors who are registered at the Tax Office (KPP) Pratama Malang Utara. There are 100 respondents who were used as samples in this study. This study uses multiple regression analysis. The results of this study are that simultaneously, the variable level of understanding, compliance and firmness of sanctions has an effect on taxation obligations. Partially the level of understanding variable has a positive and significant effect on taxation obligations. Partially, the Compliance variable does not have a significant effect on Tax Liability. Partially the Firmness of Sanctions variable has a positive and significant effect on Taxation Obligations  Keywords: Level of Understanding, compliance and strictness of tax sanctions, tax obligations